Digital Games for Education: When Meanings Play - de Castell, Suzanne; Jenson, Jennifer (Intermédialités / Intermediality)

(untitled) (Centre de recherche sur l'intermédialité, 2007)
This paper documents the development of an educationally focused webbased game, Contagion, detailing how such a practical development project has led us to retheorize questions about what is “educational,” and how and in what ways that relates to the ludic. With reference to and within the framework of design-based research, we detail here the challenges we encountered designing this “alternative” game, and how we came to see content, not simply as “what the game is about” but as essentially tied to and enacted through all aspects of the game. We argue that content, i.e. educationally valuable knowledge, is infused through all relational aspects of the game as the player's activities accomplishments: character selection, art, narrative, programming, goals, game structures and play.